Benchmark calculations of the energies for binding excess electrons to water clusters - Vysotskiy, Victor P.; Cederbaum, Lorenz S. (Journal of chemical theory and computation, 2012)
State-of-the-art ADC(2), EOM-EA-CCSD, and EOM-EA-CCSD(2) many-body methods are used to calculate the energies for binding an excess electron to selected water clusters up to (H2O)24 in size. The systems chosen for study include several clusters for which the Hartree-Fock method either fails to bind the excess electron or binds it only very weakly. The three theoretical methods are found to give similar values of the electron binding energies. The reported electron binding energies are the most accurate to date for such systems, and these results should prove especially valuable as benchmarks for testing model potential approaches for describing the interactions of excess electrons with water clusters and bulk water.